2012
DOI: 10.1155/2012/294530
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Is Low in Secondary School Children in Fiji

Abstract: The health and wellbeing of children in lower-income countries is the focus of much international effort, yet there has been very little direct measurement of this. Objective. The current objective was to study the health-related quality of life (HRQoL) in a general population of secondary school children in Fiji, a low middle-income country in the Pacific. Methods. Self-reported HRQoL was measured by the Pediatric Quality of Life Inventory 4.0 in 8947 school children (aged 12–18 years) from 18 secondary schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 47 publications
3
22
1
Order By: Relevance
“…In this study, the HRQoL index was 70.0, which is comparable to other studies (Haraldstad et al, 2011; Petersen et al, 2012). However, it contradicted the results of Svedberg et al (2013), in which the HRQoL index was good.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, the HRQoL index was 70.0, which is comparable to other studies (Haraldstad et al, 2011; Petersen et al, 2012). However, it contradicted the results of Svedberg et al (2013), in which the HRQoL index was good.…”
Section: Discussionsupporting
confidence: 90%
“…Adolescents aged 12 to 14 years have scored higher on the HRQoL (physical and psychological well-being, moods and emotions, self-perception, school environment, and autonomy dimensions) than older groups (aged 15-18 years). Petersen et al (2012) found that lower social and physical quality of life were reported among 12- to 14-year-old adolescents, while adolescents aged between 15 and 18 years reported lower quality of life in emotional and school functioning. Moreover, a decrease in HRQoL was reported among adolescents after 12 years of age, and female adolescents have complained of stronger declines in the physical, psychological, and mood and emotion dimensions (Bisegger, Cloetta, von Bisegger, Abel, & Ravens-Sieberer, 2005; Svedberg, Eriksson, & Boman, 2013).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Again the differences were most salient with regard to functioning and well‐being in school, and in grade 9 also regarding financial recourses. Similar results were reported in a study from Fiji, establishing lower HRQOL, particularly lower school functioning and well‐being, in the indigenous group compared to the rest of the population .…”
Section: Discussionsupporting
confidence: 88%
“…Investigations of child-HRQoL in general populations, including socio-demographic variations, are particularly limited and the evidence is almost exclusively reliant on data from upper-middle or high-income (higher income) countries, primarily in the West ( 6 ). This evidence may not be directly transferable to low- or lower-middle income (lower income) countries, or non-Western cultures.…”
mentioning
confidence: 99%